PERAN MICROFINANCE DALAM KETAHANAN PANGAN - Wina Christina (Fakultas Bisnis UKDW, 2009)
Recently, food tenacity becomes big issue in Indonesia- Food tenacity not only deals with food wailability for people but also how people have access to food. One of obstacles faced by farmer is the dfficulties for them to hqve access to funding fromgovernment and private. Microfinance is one of the best alternatives of funding for farmer. This paper investigates how microfinance play important role for supporting the productivity of farmer in Indonesia. Higher productivity will increase farmer revenue ond it will lead to increasefood tenacity in Indonesia.Keywords : microfinance, productivity, food tenacity, micro credit